USE OF VIDEOLAPAROSCOPY IN ACUTE INTESTINAL OBSTRUCTION - Tulyaganov Davron Bakhtiyarovich; Shukurov Bobir Ibrahimovich; Pulatov Dilmurod Tukhtabayevich; Abdulakhatov Murodjon Khamidovich; Khoshimov Diyor Egamkulovich; Yarov Jakhongir Bakhodirovich (Scholar Express Journals, 2023)
Comparative analysis of the results of open and laparoscopic interventions in patients with different forms of acute intestinal obstruction (AIO).
Keywords: Acute intestinal obstruction; adhesion obstruction; treatment; videolaparoscopy